Triple hierarchical micro–meso–macroporous carbonaceous foams bearing highly monodisperse macroporosity. (September 2015) - Ungureanu, Simona; Birot, Marc; Deleuze, Hervé; Schmitt, Véronique; Mano, Nicolas; Backov, Rénal
Abstract: The limited coalescence phenomenon occurring in Pickering emulsions stabilized by solid particles allows preparing monolithic silica foams with nearly monodisperse macroscopic voids and also meso- and microporosities. After soaking of these foam hard templates with a phenolic resin, partially graphitized interconnected porous carbon monoliths can be obtained easily. Like the silica templates, these carbon monoliths possess a hierarchical, triple porosity. Mercury intrusion porosimetry reports a macropore volume fraction of 45–70% with a narrow pore size distribution, while their specific surface area values lie between 700 and 900 m 2  g −1 and their mesopore specific surface area between 200 and 500 m 2  g −1 . This approach allows preparing hierarchical porous carbon whose mesoporosity does not require using any soft template to organize the resin precursor.